Exploring the Influence of Land Use Types on Soil Properties at Arjo-Dhidhessa Sugar Estate, Western Ethiopia - Workina Geleta Likasa; Fekadu Fufa Feyessa; Abdissa Bekele Sima (Applied and Environmental Soil Science)
This study examined the influence of land use types and soil depth on soil’s physicochemical properties in the Sugar Estate of Arjo-Dhidhessa, western Ethiopia. This study aimed to provide baseline data for future investigations in the study area by exploring significant soil quality indicators across various land use types and soil depths. Fifteen composite soil samples were collected from selected land use types, including fallow land, cropland, irrigated land, forest land, and shrubland, at three different soil depths (0–30, 30–60, and 60–90 cm). Particle size distribution; bulk density (ρb); total porosity (Tp); pH; organic soil matter; and available texture and phosphorus. The exchangeable acidity (EA), cation exchange capacity, and exchangeable bases (EBs) were found to be influenced by land use changes and soil depth. The results revealed that the bulk density (1.43 g/cm2) is highest in the cropland subsurface, whereas forest lands tend to have a relatively high clay content (67%), moisture content (25.74%), and Tp (54.28%). While the pH of irrigated land was 5.17, that of fallow land, cropland, and forest land varied from 5.47 to 5.84. Compared with the other land uses, the forest and shrubland areas presented higher levels of soil organic matter (SOM) (2.49%) and total nitrogen (TN) (0.126%). Forest land presented relatively high SOM (2.45%), TN (0.126%), available phosphorus (AvP) (1.36%), and exchangeable calcium (Ca2+) levels (16.82 cmol/kg), whereas irrigated land had presented the lowest amounts (5.22 mg/kg), Ca2+ (3.97 cmol/kg), and exchangeable magnesium (Mg2+) (0.99 cmol/kg). In contrast, agricultural activities were found to significantly reduce soil quality, as evidenced by higher bulk densities in cropland and irrigated land as well as lower levels of nutrients, including AvP and EBs, primarily due to erosion and crop harvesting. To maintain and improve soil pH and AvP levels, it is essential to adopt sustainable land management practices that contribute to maintaining higher phosphorus levels and improving overall soil fertility.